KARAKTERISASI KAPASITOR BARIUM STRONTIUM TITANAT (BST) Ba0,75 Sr0,25 TiO3 , YANG DIBUAT MENGGUNAKAN METODE SOL-GEL - Rahmi Dewi; Tiara Pertiwi; Krisman Krisman (Komunikasi Fisika Indonesia, 2019)
The thin film of Barium Strontium Titanate (BST) has been studied withcomposition ofby using sol-gel method that annealed in temperature of 600oC and 650oC. The thin film of BST is characterized by using Field Emission Scanning Electron Microscopy (FESEM) and an impedance spectroscopy. The results of  FESEM characterization for samples in temperature of 600oC and 650oC are 55.83 nm and 84.88 nm in thickness respectively. The result of impedance spectroscopy characterization given frequency values obtained by the impedance value of real and imaginary.The capacitance value at a frequency of 20 Hz from a thin film of BST in temperature of 600oC and 650oC are 69.36Fand138.70F. The dielectric constant of the thin film of BST in temperature of 600oC and 650oC are 22.17 dan 131.56 respectively.